Formation of an intermediate during the hydrothermal synthesis of ULM-5 studied using time-resolved, in situ X-ray powder diffraction - Francis, R; Price, S; OBrien, S; Fogg, A; OHare, D; Loiseau, T; Ferey, G (1997)
In situ energy dispersive X-ray diffraction studies on the hydrothermal synthesis of the oxyfluorinated gallophos-phate, ULM-5, show that when orthophosphoric acid is used as a starting material ULM-5 forms rapidly after an initial induction period, whereas when phosphorus pentoxide is used as a starting material a previously unobserved crystalline intermediate is formed, which subsequently reacts to form ULM-5; conditions have been identified in which this intermediate is relatively long lived and this has allowed the subsequent isolation of a pure sample of this intermediate.